Synthesis and Spectral Studies on Transition Metal Complexes Derived from a Physiologically Active Macrocyclic Ligand - Venkateswar Rao, P.; Ashwini, K.; Fatima, Kaneez (Asian Journal of Chemistry, 2010)
Complexes of VO(II), Mn(II), Fe(II), Co(II), Ni(II) and Cu(II) with a new ligand N-1-[(Z)-1-(2-hydroxy-6-methyl-4-oxo-4H3-pyranyl) ethyli-dene]-1-hydrazene carbothiohydrazide (HEHCTH) of composition [ML·xH2O], where L = HEHCTH, x = 0 or 2, have been synthesized. The Cu(II) and Ni(II) complexes have been assigned square planar geometry, the Mn(II), Fe(II) and Co(II) complexes octahedral geometry and VO(II) complex is assigned a square pyramidal geometry. The ligand and the metal chelates have been screened for antibacterial activity.